2015
DOI: 10.1016/j.juro.2014.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α is a Key Mediator and Therapeutic Target for Bladder Complications of Benign Prostatic Hyperplasia

Abstract: Purpose While estrogens are important in prostate growth and play a role in benign prostatic hyperplasia (BPH), no current therapies directly target estrogen action. Estrogens act primarily via estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ). Using a mouse model, we evaluated the relative contribution of these receptors to bladder complications of BPH. We also evaluated prevention of these bladder complications by selective estrogen receptor modulators (SERMs), raloxifene and tamoxifen (ERα sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Fifty percent of men over the age of 50 will have BPH, while 90% of men at age of 80 will have an enlarged prostate [3]. While aging and androgens are considered to have a role in BPH development [4], the role of other risk factors, namely, inflammation [5], inflammatory mediators, oxidative stress, hormones [6], physical activity, dietary factors, cardiovascular disease, obesity and diabetes [7] had been under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty percent of men over the age of 50 will have BPH, while 90% of men at age of 80 will have an enlarged prostate [3]. While aging and androgens are considered to have a role in BPH development [4], the role of other risk factors, namely, inflammation [5], inflammatory mediators, oxidative stress, hormones [6], physical activity, dietary factors, cardiovascular disease, obesity and diabetes [7] had been under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…We recently tested the SERMs raloxifene and tamoxifen for prevention of bladder complications in male mice treated with T+E 2 . While raloxifene prevented both bladder enlargement and prostate growth, an ERβ antagonist did not [32]. These results support that ERα is both a key mediator and therapeutic target in BPH.…”
Section: Serms As Therapeutics For Bph-lutsmentioning
confidence: 79%
“…In a small cohort of elderly men, raloxifene was well tolerated but did not affect markers of bone turnover or lipid levels [43]. While we did not compare efficacy of raloxifene and tamoxifen in BPH prevention directly, we demonstrated that raloxifene decreased both bladder and prostate mass in the male mouse treated with T+E 2 [32]. It is unknown whether treatment with raloxifene will reverse BPH-LUTS, once established, in animal models.…”
Section: Serms As Therapeutics For Bph-lutsmentioning
confidence: 98%
See 2 more Smart Citations